1982
DOI: 10.1007/bf03339114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strip Velocity on Pickling Rate of Hot-Rolled Steel in Hydrochloric Acid

Abstract: SUMMARYThe combined effect of strip velocity with other parameters on pickling rate of hot-rolled low-carbon steel in hydrochloric acid (HCl)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…The temperature of the liquid also influences the pickling rate: higher temperature reduces the pickling time, but the influence of the temperature may be disregarded since the temperature is maintained relatively constant due to the heat exchanger. Hudson and Warning (1982) have shown that the pickling time decreases when the strip velocity increases. However, above a certain strip velocity limit, the pickling time is constant.…”
Section: Description Of the Processmentioning
confidence: 95%
See 1 more Smart Citation
“…The temperature of the liquid also influences the pickling rate: higher temperature reduces the pickling time, but the influence of the temperature may be disregarded since the temperature is maintained relatively constant due to the heat exchanger. Hudson and Warning (1982) have shown that the pickling time decreases when the strip velocity increases. However, above a certain strip velocity limit, the pickling time is constant.…”
Section: Description Of the Processmentioning
confidence: 95%
“…However, the pickling rate is not noticeably influenced by the concentration of ferrous salt. Overpickling is prevented by adding a special inhibitor to the pickling acid (Hudson & Warning, 1982). In addition there are other parameters which influence the pickling rate, for example, the oxide thickness, strip temperature and type of metal.…”
Section: Description Of the Processmentioning
confidence: 99%
“…Liu Jiang [6] hold opinions that the acid temperature is a function of the best strip speed, and the acid liquid turbulence is also the function of acid temperature. Hudson [7][8][9]had studied the effects of acid concentration, temperature and speed of the strip on acid pickling time, and think that when the acid temperature is low, elongation rate for pickling promotion effect is obvious. But when the temperature is high, the effect of elongation rate to enhance the speed of picking is weak.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many researchers have shown keen interest in investigating the corrosive behavior of low carbon steel in an acid environment. Among the mineral acids, hydrochloric acid is generally used in pretreatment of metallic components (Hudson & Warning, 1980;Kaan Emregul & Hayvali, 2006).…”
Section: Introductionmentioning
confidence: 99%